2020
DOI: 10.1186/s13000-020-00946-8
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-484 is associated with poor prognosis and tumor progression of gastric cancer

Abstract: Background: Gastric cancer is one of the most common cancers leading to high cancer mortality. MicroRNA-484 (miR-484) has been evaluated as a biomarker for various types of cancers. The subject of this study is to investigate the functional role of miR-484 in gastric cancer. Methods: The expression of miR-484 in gastric cancer was analyzed by quantitative real-time polymerase chain reaction (qRT-PCR) assay. Kaplan-Meier survival and Cox regression analyses were employed to explore the prognostic significance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Gastric cancer (GC) is one of the most common cancers causing cancer mortality, especially in Asian populations, and poses a serious threat to human life. Recent clinical data confirmed that miR-484 was significantly downregulated in GC tissues compared to paraneoplastic tissues, and similarly, GC cell lines showed a typical decrease in miR-484 expression (35,104). Surprisingly, GC tissue miR-484 low levels were closely associated with hypodifferentiated or undifferentiated cells, distant metastasis in lymph nodes, and reduced 5-year overall survival (104).…”
Section: Gastric Cancermentioning
confidence: 87%
“…Gastric cancer (GC) is one of the most common cancers causing cancer mortality, especially in Asian populations, and poses a serious threat to human life. Recent clinical data confirmed that miR-484 was significantly downregulated in GC tissues compared to paraneoplastic tissues, and similarly, GC cell lines showed a typical decrease in miR-484 expression (35,104). Surprisingly, GC tissue miR-484 low levels were closely associated with hypodifferentiated or undifferentiated cells, distant metastasis in lymph nodes, and reduced 5-year overall survival (104).…”
Section: Gastric Cancermentioning
confidence: 87%
“…Recently, the rapid rise of immunotherapy has brought a new therapeutic landscape for the patients who didn’t benefit from conventional chemotherapy, radiation or surgery ( Chivu-Economescu et al, 2018 ). However, in clinical practice, the majority of GC patients were usually still lack of effective therapeutical response to immunotherapy ( Li et al, 2020 ). Therefore, it is crucial to screen reliable index especially immunotherapy-related biological parameters that can predict the therapeutic responses to immunotherapy of GC patients.…”
Section: Introductionmentioning
confidence: 99%
“…27 In previous studies, miR-484 has been proved to be a tumor suppressor in several cancers, such as cervical cancer and gastric cancer. 28,29 In this study, we found that PCED1B-AS1 can function as ceRNA for miR-484 to inhibit its expression. What is more, miR-484 overexpression inhibited the proliferation and migration of ccRCC cells and EMT process.…”
Section: Discussionmentioning
confidence: 64%